Intervensi dalam Mengendalikan Ketidakstabilan Glukosa Darah pada Asuhan Keperawatan Pasien Diabetes Melitus Tipe 2 di Masyarakat ; Literatur Review - Israfil (Jurnal Keperawatan Muhammadiyah, 2025)
Objective: This study aims to identify various types of interventions in controlling unstable blood glucose levels in the care of type 2 diabetes mellitus patients in the community. Method: literature review research design, literature sources are research articles on the Google Scholar or Google Cendikia database, and Researchgate. The literature search used the keywords "Nursing Intervention" and "Nursing Care" and "Instability" and "Blood Glucose" and "Diabetes Mellitus". Literature selection used a non-systematic method, with inclusion criteria using the PEOS approach, namely Population: type 2 diabetes mellitus patients in Indonesia, Exposure: interventions in nursing care, Outcome : blood glucose levels, Study Design: case study. Results: 557 were found in the search and 16 articles were designated as data. The results of the study found that interventions in controlling blood glucose in the maintenance of diabetes mellitus patients were relaxation interventions, physical exercise interventions, and spiritual interventions. Relaxation interventions include Benson relaxation, progressive muscle relaxation, and autogenic relaxation. Physical exercise interventions include diabetic foot exercises, walking exercises, and tai chi exercises. Spiritual interventions include dhikr and murottal of the Qur’an. Conclusion: Physical exercise intervention is able to control blood glucose directly by converting blood glucose into energy during therapy. Relaxation interventions are able to control blood glucose indirectly by controlling stress as a trigger for hyperglycemia, and spiritual interventions are able to control blood glucose indirectly by increasing the patient's self-efficacy and ability to care for themselves. These various interventions can be an option for nurses to control blood glucose levels when caring for patients with type 2 diabetes mellitus in the community.